Implementation of Culinary Arts Learning as a Medium for Developing Life Skills for Vocational High School Students in Tomohon City, North Sulawesi Province - Louisa Kandoli (Indonesian Journal Publisher, 2025)
This study aims to examine and synthesise previous research on the implementation of culinary arts learning as a medium for developing students' life skills in vocational high schools (SMK) in Tomohon City, North Sulawesi Province. This study employed a literature review with a qualitative analysis approach. The literature search was conducted using Publish or Perish, a free platform integrated with Google Scholar. Keywords used included